Recent Painting USA : The Figure. - Bareiss, Walter; Jones, Anne K.; Columbus Gallery of Fine Arts, Columbus; Colorado Springs Fine Arts Center, Colorado Springs; Baltimore Museum of Art, Baltimore; City Art Museum of St. Louis; San Francisco Museum of Art, San Francisco; Walker Art Center, Minneapolis (New York : The Museum of Modern Art, 1962)
Alken, William ; Altman, Harold ; Beauchamp, Robert ; Beery, Gene B. ; Berger, Fred ; Bischoff, Elmer ; Blaustein, Al ; Borge, Ralph W. ; Bouché, René ; Boynton, James ; Broderson, Robert M. ; Brody, Lilly ; Bushnell, Kenneth ; Button, John ; Clutz, William ; Cohen, George ; Covington, Harrison ; De Kooning, Elaine ; de Niro, Robert ; Back, Charles S. Du ; Eades, Luis ; Floyd, Stanley ; Giobbi, Edward ; Golub, Leon ; Golubov, Maurice ; Goodman, Sidney ; Goodwin, Charles Bennett ; Grippi, Salvatore ; Gunther, George W. ; Hansen, Robert ; Hennessey, James ; Hirsch, Joseph ; Hornaday, Richard ; Jergens, Robert ; Johnson, Lester ; Kamihira, Ben ; Kern, Arthur ; Kirschenbaum, Jules ; Koppelman, Chaim ; Koppelman, Dorothy ; Landau, Jacob ; Lanyon, Ellen ; Leake, Eugene ; Lidov, Arthur ; Lifson, Hugh A. ; Lindner, Richard ; Maddox, Jerrold ; Marsicano, Nicholas ; Garrell, James Mc ; McLarty, Jack ; Narotzky, Norman ; Nelson, Robert A. ; Oliveira, Nathan ; Pato, Barbara ; Pinkerton, Clayton ; Pollack, Reginald ; Rivers, Larry ; Rossman, Ruth Sharff ; Ruhtenberg, Cornelis ; Schnurr-Colflesh, Elinore ; Schwartz, Manfred ; Seidenberg, Jean ; Sherman, Sarai ; Solbert, Ronni ; Stussy, Jan ; Treiman, Joyce ; Van Dyk, James ; Wesselmann, Tom ; Wheat, John ; Williams, Hiram ; Wines, James ; Wonner, Paul ; Yektai, Manoucher ; Zajac, Jack
biografie
Recent Painting USA : The Figure, The Museum of Modern Art, New York, May 23, 1962 - September 4, 1962 ; Columbus Gallery of Fine Arts, November 1, 1962 - November 29, 1962 ; Colorado Springs Fine Arts Center, January 30, 1963 - February 27, 1963 ; Baltimore Museum of Art, March 15, 1963 - April 26, 1963 ; City Art Museum of St. Louis, May 13, 1963 - June 10, 1963 ; San Francisco Museum of Art, August 18, 1963 - September 15, 1963 ; Walker Art Center, October 1, 1963 - November 12, 1963
Engels
boek
Keywords: Amerika